The Neguev revisited: a study of the agricultural changes between 1987 and 1996 in the Neguev settlement, Costa Rica - Kuiper, M. (1997)
76 pág, 2 ilus, 56 tab, 17 ref. También como: Field Report - Atlantic Zone Programme (CATIE) no. 155